Room-Temperature On-Spin-Switching and Tuning in a Porphyrin-Based Multifunctional Interface - Sturmeit, Henning Maximilian; Cojocariu, Iulia; Windischbacher, Andreas; Puschnig, Peter; Piamonteze, Cinthia; Jugovac, Matteo; Sala, Alessandro; Africh, Cristina; Comelli, Giovanni; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; et al. (Small, 2021)
Molecular interfaces formed between metals and molecular compounds offer a great potential as building blocks for future opto-electronics and spintronics devices. Here, a combined theoretical and experimental spectro-microscopy approach is used to show that the charge transfer occurring at the interface between nickel tetraphenyl porphyrins and copper changes both spin and oxidation states of the Ni ion from [Ni(II), S = 0] to [Ni(I), S = 1/2]. The chemically active Ni(I), even in a buried multilayer system, can be functionalized with nitrogen dioxide, allowing a selective tuning of the electronic properties of the Ni center that is switched to a [Ni(II), S = 1] state. While Ni acts as a reversible spin switch, it is found that the electronic structure of the macrocycle backbone, where the frontier orbitals are mainly localized, remains unaffected. These findings pave the way for using the present porphyrin-based system as a platform for the realization of multifunctional devices where the magnetism and the optical/transport properties can be controlled simultaneously by independent stimuli.
CRIS-Team Scopus Importer:2021-10-22
Keywords: charge transfer; functionalization; molecular interfaces; spin switching; spintronics